Spanish American Women's Use of the Word : Colonial through Contemporary Narratives - Schlau, Stacey, 1948- (Book collections on Project MUSE., 2001)
"Women's participation, both formal and informal, in the creation of what we now call Spanish America is reflected in its literary legacy. Stacey Schlau examines what women from a wide spectrum of classes and races have to say about the societies in which they lived and their place in them." "Schlau has written the first book to study a historical selection of Spanish American women's writings with an emphasis on social and political themes. Through their words, she offers an alternative vision of the development of narrative genres - critical, fictional, and testimonial - from colonial times to the present."--Jacket.